Assessment of the safety and ease of use of the naloxone auto-injector for the reversal of opioid overdose - Merlin, Mark A (Open Access Emerg Med, 2015)
Over the last decade, opioid-related deaths in the United States have increased at an alarming rate. The use of naloxone by laypersons is a newer concept and its utilization can benefit patients by rapid administration due to it being readily available immediately after an opioid overdose. The US Food and Drug Administration approved a naloxone auto-injector on April 3, 2014 for adults and pediatrics, designed for use by anyone including patients, family members, bystanders, and medical professionals. This device (EZVIO™) is the first device of its kind available on the market. The auto-injector is a battery-operated disposable 0.4 mg/0.4 mL prefilled device for use in the lateral thigh by patients, bystanders, or health care professionals. It utilizes auditory and visual commands for ease of administration and instructs patients to seek further medical care after injection. EVZIO costs about $600 for two auto-injectors and a trainer. Additionally, in August 2013, the Substance Abuse and Mental Health Services Administration introduced the Opioid Overdose Toolkit, a federal resource promoting safety and prevention information. This extensive document provides information for medical professionals, first responders, patients, caregivers, and overdose survivors. It outlines many strategies for dealing with this health care crisis. Most importantly, it highlights the importance of rapid recognition and treatment of opioid overdoses as well as routine conversations with patients assessing the need for naloxone prescriptions. The auto-injector is a safe, portable device with limited instruction needed and should routinely be made available to anyone who has contact with an opioid user.